The Relationship Between Lifestyle and Hygiene Habits on the Occurrence of Flour Albus Among Adolescents at Mad-rasah Aliyah Hj. Haniah in 2024 (International Forum of Researchers and Lecturers, 2025)
Approximately 75% of women worldwide will experience flour albus at least once in their lifetime, and 45% will experience it twice or more. According to Riskesdas data, the prevalence of flour albus among women of reproductive age reached 58.6% in 2016, increased to 60.3% in 2017, and further rose to 62.9% in 2018. Research Objective: To determine whether there is a relationship between lifestyle and hygiene habits with the incidence of flour albus in adolescents at Madrasah Aliyah Hj. Haniah in 2024. Method: This study used an experimental method with a quantitative approach and a cross-sectional study design. Results: The study found that among 68 respondents, there was no relationship between lifestyle and flour albus. However, there was a relationship between hygiene habits and flour albus. Conclusion: There is no relationship between lifestyle and flour albus, but there is a relationship between hygiene habits and flour albus.